2021
DOI: 10.3389/fphar.2021.730312
|View full text |Cite
|
Sign up to set email alerts
|

Selective STAT3 Inhibitor Alantolactone Ameliorates Osteoarthritis via Regulating Chondrocyte Autophagy and Cartilage Homeostasis

Abstract: Osteoarthritis (OA), which is identified by chronic pain, impacts the quality of life. Cartilage degradation and inflammation are the most relevant aspects involved in its development. Signal transducer and activator of transcription 3(STAT3), a member of the STATs protein family, is associated with inflammation. Alantolactone (ALT), a sesquiterpene lactone compound, can selectively suppress the phosphorylation of STAT3. However, the pharmacological effect of ALT on OA is still imprecise. In this study, IL-1β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…IL-1β induced increased OA-related protein expressions in a time and concentration dependent manner ( Tu et al, 2019 ). The stimulation of IL-1β (10 ng/ml) for 24 h could induce inflammation in chondrocytes ( Wang et al, 2019 ; Pei et al, 2021 ). IL-1β has been shown to induce the overproduction of iNOS and COX-2, which is directly relevant to the secretion of nitric oxide (NO) and prostaglandin E2 (PGE2) ( Sheu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β induced increased OA-related protein expressions in a time and concentration dependent manner ( Tu et al, 2019 ). The stimulation of IL-1β (10 ng/ml) for 24 h could induce inflammation in chondrocytes ( Wang et al, 2019 ; Pei et al, 2021 ). IL-1β has been shown to induce the overproduction of iNOS and COX-2, which is directly relevant to the secretion of nitric oxide (NO) and prostaglandin E2 (PGE2) ( Sheu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various natural compounds appear to be efficacious in bone-related diseases and hold promise as a succedaneum for synthetic compounds as the next generation of therapeutic agents. Alantolactone and lycopene inhibit IL-1 β -induced activation of NF-κB and Stat3 and attenuate chondrocyte autophagy and extracellular matrix (ECM) degradation ( Pei et al, 2021 ; Zhan et al, 2021 ). Alantolactone at 2 mg/kg alleviated medial meniscus wear and MMP13-positive cell counts in vivo ( Pei et al, 2021 ).…”
Section: Target Signal Transducer and Activator Of Transcription 3 Si...mentioning
confidence: 99%
“…Alantolactone and lycopene inhibit IL-1 β -induced activation of NF-κB and Stat3 and attenuate chondrocyte autophagy and extracellular matrix (ECM) degradation ( Pei et al, 2021 ; Zhan et al, 2021 ). Alantolactone at 2 mg/kg alleviated medial meniscus wear and MMP13-positive cell counts in vivo ( Pei et al, 2021 ). By focusing on macrophages in post-trauma OA, Tian et al found that angelicin could adjust the M1/M2 ratio in synovial tissue and protect articular cartilage through the CD9/gp130/Stat3 pathway ( Tian et al, 2021 ).…”
Section: Target Signal Transducer and Activator Of Transcription 3 Si...mentioning
confidence: 99%
“…In addition, there are a few studies concerning about the correlation between ALT administration and cell autophagy in cancer cells. ALT could play a significant role in promoting impaired autophagy, facilitating to allay osteoarthritis and strengthen pancreatic cancer cells' chemosensitivity (He et al, 2018;Pei et al, 2021). Another two studies have demonstrated that treatment with ALT could significantly downregulate the cell autophagy in ALL and liver cancer cells, implying that ALT have the potential to kill cancer cells through modulating autophagy (Kang et al, 2019;Shi et al, 2020).…”
Section: Implication Of Alt For Cancer-associated Signaling Pathwaysmentioning
confidence: 99%